Prevalencia de nematodos gastrointestinales en felinos de la ciudad de Machala - Morales Rambay, Gerardo Andrés (2015)
The investigation of gastrointestinal nematodes in cats took place in the city of Machala El Oro province, during the months of November 2014 to March 2015 based on the following objectives: 1) to establish the prevalence of gastrointestinal nematodes in cats in urban parishes the city of Machala, 2) Establish the prevalence of Gastrointestinal Nematodes in cats by area, habitat, sex, diet and age, 3) Develop an epidemiological map of the city of Machala.The methodology used in this work, consisted to subdivide Machala in different parishes taking significant samples of each sector thereby creating a common sample and in this way obtaining the results presented.In summary result it was obtained in Machala of 366 individuals tested a total of 50.55% prevalence of infected Gastrointestinal Nematodes. Proving that the highest percentage found in Pto. Bolivar with 73.17% of infected individuals, the percentage of female animals with 71.25% proved to be the sector most affected by the sex of the individual, the type of homemade food proved to have a higher prevalence covering a percentage equivalent to 57.26%, in terms of habitat in which the individuals analyzed were developed we noticed that the area with the most affected was the extra home habitat with a strong 95.83% of affected individuals and finally with respect to kind parasite Ancylostoma is located in the first place as the most prevalent Gastrointestinal Nematode samples with a percentage of 55.14% of affected individuals.Finishing with these investigations is expected that all these data will serve the community for subsequent works, investigations and projects.